SPECIFICITY OF PROFESSIONAL TRAINING OF FUTURE MUSIC ART`S TEACHERS TO INSTRUMENTAL-PERFORMING ACTIVITY - Kasilov, Ivan (Continuing Professional Education: Theory and Practice, 2019)
The article is devoted to main problems of professional training, concerning of instrumental-performing activity of Music art`s teachers in conditions of music-pedagogic education in Ukraine. The title of the text shows necessity of consideration and detailed analysis this problem in research works of well-known authors also. The article begins with a short discussion, relatively of understanding of instrumental-performing activity as a contemporary pedagogic problem in the system of higher education. The introductory part deals with necessity of implementation of global reforms in the content of Ukrainian pedagogic education. The problem of orientation of Ukrainian society to democratic values in the conditions of joining to the Bologna agreement is considered. The aim of the article is to determine of specificity of instrumental-performing activity as the optimal methodology, directed to resolution of complex music-performing tasks. The next paragraph describes the main methodical ways, directed to resolution of the problem questions, concerning of instrumental-performing activity in terms of professional training of Music art`s teachers at the pedagogic universities. Further the author reports that structure of instrumental-performing activity consists from next specific features, such as: physiologic peculiarity of performing apparatus; formation of performer`s polyphonic thinking; systematic training during playing the musical instrument; gradual complication of music repertoire; use of various styles and genres in the process of professional training. According to the text, contemporary higher education should to resolve the tasks, directed to development of student`s personal music abilities as a future teacher-musician. The final paragraph ends with conclusion, which generalizes importance of use of all specific features of instrumental-performing activity for attainment of positive results in the process of professional training of future Music art`s teachers at the educational system of pedagogic universities.